The Effect of Corneal Refractive Power Area Changes on Myopia Progression during Orthokeratology. (16th June 2022) - Chen, Minfeng; Liu, Xinting; Xie, Zhu; Wang, Pengqi; Zheng, Miaoran; Mao, Xinjie
Abstract : Purpose . To investigate the effect of corneal refractive power area changes on myopia progression during orthokeratology. Methods . One hundred and sixteen children who met the inclusion criteria and insisted on wearing orthokeratology lenses for two years were retrospectively assessed. Seventy-two children with the orthokeratology lens decentration distance more than 0.5 mm but less than 1.5 mm were in the decentered group, and forty-four children with the orthokeratology lens decentration distance less than 0.5 mm were in the centric group. The orthokeratology decentration via tangential difference topography was analyzed. This study calculated the different power areas in the central 4 mm pupillary area by axial-difference corneal topography, compared the differences of the different power areas between these two groups, and evaluated the relationships between corneal positive-power area, orthokeratology decentration, and AL changes. Results . The axial length changes of the centric group presented a statistical difference with the decentered group (0.52 ± 0.37 mm vs. 0.38 ± 0.26 mm; t = 2.403, p = 0.018 ). For all children, both the AL changes (0.43 ± 0.31 mm) and decentration distance (0.64 ± 0.33 mm) showed a significant correlation with the positive-power area ( r = −0.366, p < 0.001 and r = 0.624, p < 0.001 ); AL changes also presented a statistical correlation with decentration distance ( r = −0.343, p < 0.001 ), baseline age ( r = −0.329, p < 0.001 ), and baseline spherical equivalent refractive power ( r = 0.335, p < 0.001 ). In the centric group and decentered group, the AL changes (centric group: r = −0.319, p = 0.035 ; decentered group: r = −0.332, p = 0.04 ) and decentration distance (centric group: r = 0.462, p = 0.002 ; decentered group: r = 0.524, p < 0.001 ) had a significant correlation with the positive-power area yet. In the multiple regression analysis, AL changes were increased with less baseline age (beta, 0.015; p < 0.001 ), positive-power area (beta, 0.021; p = 0.002 ), and larger SER (beta, 0.025; p = 0.018 ). Conclusions . The corneal positive-power area had a positive impact on affirming AL changes during orthokeratology. This area might be formed by lens decentration to provide an additional myopia-defocusing influence on the retina to achieve better myopia control.